From “Primitive Religion” to Cognitive Universal: Decolonizing the study of African Traditional Religions - Saheed Anuoluwapo Agunbiade (Journal of Religion and Decoloniality, 2026)
The marginalization of African Traditional Religions (ATRs) by Western scholarship and colonial authorities has long undermined their identity and legitimacy. Historically, ATRs have been the foundation of African society, shaping values, principles, worship practices, and philosophical outlooks. With the advent of Westernization through colonialism and imperialism, ATRs were labeled “fetishistic”, “primitive” , “superstitious”, and “inhumane”, mischaracterizations that delegitimized indigenous spirituality while promoting Western Christian traditions as superior. This ethnocentric bias alienated Africans from their religious heritage and eroded their cultural identity. While many ATR practices have parallels in Western religions, yet one has been privileged over the other to justify cultural domination. This paper employs the Cognitive Science of Religion (CSR) as a theoretical framework to interrogate these ethnocentric biases. CSR emphasizes universal cognitive mechanisms underlying religious thought, providing a platform to reinterpret ATRs as expressions of shared human cognitive capacities rather than exotic deviations from a normative standard. Through comparative and conceptual analysis, the paper argues that indigenous epistemologies,rooted in oral traditions, communal values, and relational ontologies, embody complex cognitive strategies comparable to those of any religion. By dismantling the “primitive” stereotype, this paper situates ATRs within a global discourse that recognizes their philosophical sophistication, cognitive legitimacy, and cultural resilience, thereby advancing a more inclusive and methodologically pluralist study of religion.